Impact of different growing media and Gibberellic acid (GA3) concentrations on rough lemon (Citrus jambhiri) seed germination and its growth attributes - Rashad Qadri, Shahzad Hussain, Muhammad Tahir Akram, Muhammad Azam Khan, Muhammad Mumtaz Khan, Khalid Hussain, Muhammad Ahsan Khatana, Shahid Nadeem, Umais Asghar Khan (International Journal of Modern Agriculture, 2021)
Citrus is among one of the most important and widely grown fruit crops that is cultivated worldwide. The rootstocks of citrus have a significant impact on the yield and quality of fruits. Therefore, before selecting a proper rootstock, a number of its attributes and characteristics are evaluated such as, vigor, yield, rooting ability. Gibberellic acid (GA3) is an environment-friendly growth regulator that is being used in multiple fruits crops to enhance phenotypic traits. In this study, an experiment was conducted to explore the influence of various GA3 concentrations and different growth media to check their influence on germination percentage and growth attributes of rough lemon. The experiment was laid as a completely randomized design (CRD) under two factorial arrangements. The results revealed that seeds treated with GA3 @ 400 ppm concentration and grown in S5 media (sand, silt and leaf manure) enhanced maximum seed germination (%), plant height (cm), stem diameter (mm), number of leaves, number of roots, root length (cm) and seedling fresh weight (g). Over all among GA3 concentrations, GA3 @ 400 ppm concentration was most predominated followed by GA3 @ 200 ppm, Similarly among growing media, (S5) the combination of sand, silt and leaf manure improved seed germination and its growth parameters.